(untitled) (Strathmore Law Journal, 2020)
States are collapsing and genocidal acts are being committed or may happen any moment. In these instances, states look to the United Nations (UN) to act in order to prevent genocide from happening. This article seeks to determine if there exists an obligation under international law for the UN to prevent genocide, and in that event, can the UN be held responsible under international law for failure to comply with this obligation? This article further analyses these questions by looking at the aspect of Responsibility to Protect (R2P) which elicits an obligation to prevent genocide first to states and then to the UN. At the very minimum, every state must protect its population from genocide, war crimes, ethnic cleansing and crimes against humanity. In the case of states failing to undertake this obligation, the UN is bound to step in and undertake this obligation. Hence, this is a responsibility that is an obligation to states first and then to the UN. In summation, this article establishes that the obligation to prevent genocide is a customary international law obligation. Further, the UN is bound by this obligation. However, it is shown that the procedures that are available to address its failure to uphold this obligation are inconsequential since the UN has absolute immunity and any decision, even if holding the UN responsible, cannot be enforced as against it. Neverthless, this article provides some recommendation(s) as to how the UN can play a role in ensuring accountability for failures within its ambit.